Analisis Kepemimpinan Transformasional Dalam Inovasi Sistem Pelayanan Rakyat Sidoarjo di Pemerintah Kabupaten Sidoarjo - Moh. Daffa Nur Rizka Widiatmoko; Lukman Arif (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Sistem Pelayanan Rakyat Sidoarjo Innovation (SIPRAJA) created by the Sidoarjo Regency Government in the Informatics Regional Administration Sub-Section arose because of the opinion of the people of Sidoarjo that government services were convoluted, slow, expensive, uncertain, and tiring. This SIPRAJA innovation is included in the Top 99 nominations for National Level Public Service Innovations in 2021, where this innovation cannot be separated from the role of its leader, namely the Head of the Regional Administration Sub-Division of the Government Section of the Sidoarjo Regional Secretariat. This study uses a qualitative approach and descriptive research type. The determination of informants was carried out using purposive sampling and accidental sampling techniques. Data collection was carried out by interview, observation and documentation techniques. Presentation of data is done by grouping and combining the data obtained. The validity of the data was tested by data triangulation techniques. The results show that transformational leadership in relation to the SIPRAJA Innovation has been clearly illustrated in the Regional Administration Sub-Division of the Government Section of the Sidoarjo Regional Secretariat with the support of relevant stakeholders reaching the maximum point. Keywords: Transformational Leadership, Innovation, Sistem Pelayanan Rakyat Sidoarjo